2022
DOI: 10.1038/s41598-022-12059-x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin-coated collagen fleece versus absorbable dural sealant for sellar closure after transsphenoidal pituitary surgery: a comparative study

Abstract: Various surgical methods to prevent postoperative cerebrospinal fluid (CSF) leaks during transsphenoidal surgery have been reported. However, comparative studies are scarce. We aimed to compare the efficacy of a fibrin-coated collagen fleece (TachoSil) versus a dural sealant (DuraSeal) to prevent postoperative CSF leakage. We perform a retrospective study comparing two methods of sellar closure during endoscopic endonasal transsphenoidal surgery (EETS) for pituitary adenoma resection: TachoSil patching versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…11 Spitaels et al conducted a review and comparative analysis of Tachosil®, DuraSeal®, and other to methods to prevent CSF leak. 12 After assessing non-randomized controlled trials, they concluded that fibrin sealants are safe and are effective in preventing CSF leaks. In our study, we were able to demonstrate that Hemopatch® can be used safely as a dural sealant in cranial procedures where a watertight dural suture cannot otherwise be achieved.…”
Section: Results Baseline Demographics and Operative Parametersmentioning
confidence: 99%
“…11 Spitaels et al conducted a review and comparative analysis of Tachosil®, DuraSeal®, and other to methods to prevent CSF leak. 12 After assessing non-randomized controlled trials, they concluded that fibrin sealants are safe and are effective in preventing CSF leaks. In our study, we were able to demonstrate that Hemopatch® can be used safely as a dural sealant in cranial procedures where a watertight dural suture cannot otherwise be achieved.…”
Section: Results Baseline Demographics and Operative Parametersmentioning
confidence: 99%
“…On MINORS assessment, the 15 non‐comparative studies averaged a score of 11.6 ± 1.8 out of 16 (range: 8–14) whereas the 12 non‐randomized comparative studies scored 18.0 ± 3.4 out of 24 (range: 10–23) (Supplementary Table 1). Characteristics of all included studies were summarized in Table I 30–34,15,17,35–44,16,45–47,10,48–52 . Three studies reported level III evidence whereas the remaining 24 studies reported level IV evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of all included studies were summarized in Table I. [30][31][32][33][34]15,17,[35][36][37][38][39][40][41][42][43][44]16,[45][46][47]10,[48][49][50][51][52] Three studies reported level III evidence whereas the remaining 24 studies reported level IV evidence. Patients in the aggregate cohort were 49.0% female and, on average, 50.2 years (range: 1-87).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…The choice of the closure technique depends on the flow intensity and on the leak location, as proposed by Conger et al (34). In case of minimal diaphragm oozing, a simple treatment with a collagen sponge can be chosen (64,66,69). Collagen sponge has the great advantage to be easy to use.…”
Section: Discussionmentioning
confidence: 99%
“…( 34 ). In case of minimal diaphragm oozing, a simple treatment with a collagen sponge can be chosen ( 64 , 66 , 69 ). Collagen sponge has the great advantage to be easy to use.…”
Section: Discussionmentioning
confidence: 99%